2020
DOI: 10.1021/acs.orglett.0c00925
|View full text |Cite
|
Sign up to set email alerts
|

Colletofurans A–E, 1-Octyl-1,3-dihydroisobenzofuran Derivatives from Colletotrichum boninense AM-12-2

Abstract: 3-(3-Hydroxy-2-(hydroxymethyl)phenyl)propanoic acid, 2-hydroxymethyl-3-hydroxy-(E)-cinnamic acid, and colletofurans A−E were isolated from Colletotrichum boninense AM-12−2. Colletofurans A−E are the first natural compounds featuring a 1-octyl-1,3-dihydroisobenzofuran core. Their structures were initially established by 1D/2D-NMR and HRESITOFMS. Mosher's ester method was used to determine the absolute configurations of secondary alcohols in colletofurans A−C. The structures of colletofurans A and B−E were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In particular, chiral 1,3-dihydroisobenzofuran, commonly referred to as phthalan, is abundant in bioactive natural products, which display pharmacological properties such as antibacterial, anti-inflammatory, antidepressive, antioxidant, and anti-influenza (Figure ). Several synthetic methods have been developed for phthalans based on cyclization strategies . However, most reactions are limited to the synthesis of nonchiral phthalans.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, chiral 1,3-dihydroisobenzofuran, commonly referred to as phthalan, is abundant in bioactive natural products, which display pharmacological properties such as antibacterial, anti-inflammatory, antidepressive, antioxidant, and anti-influenza (Figure ). Several synthetic methods have been developed for phthalans based on cyclization strategies . However, most reactions are limited to the synthesis of nonchiral phthalans.…”
Section: Introductionmentioning
confidence: 99%
“…Next, a set of solvents was screened and the reaction performed in MeCN : H 2 O (800 : 1 v/v) provided the best result (Table 1, entries 1 and 8-10). Further investigation of the conditions demonstrated that the reaction could not work with n-Bu 4 NBF 4 , n-Bu 4 NClO 4 , Et 4 NBF 4 , n-Bu 4 NBr, or KI as the electrolyte (Table 1, entries [11][12][13][14][15].…”
mentioning
confidence: 99%
“…1,3-Dihydroisobenzofurans (phthalanes) widely exist in many natural products such as asperchalasines 11 and colletofurans (Scheme 1). 12 Besides, they also exist in biologically active molecules or pharmaceuticals such as citalopram and talopram, potent selective serotonin reuptake and norepinephrine transporter inhibitors, respectively. 13 As a result, a variety of synthetic approaches to 1,3-dihydroisobenzofuran derivatives have been reported.…”
mentioning
confidence: 99%
“…Benzannulated 5,5-spiroketals are relatively rare in nature (<20 reported), and a number have exhibited promising bioactivity, motivating research into their isolation and synthesis. The novel benzannulated 5,5-spiroketal paeciloketal B ( 1a ) and its epimer 1- epi -paeciloketal B ( 1b ) were discovered in 2015. These natural products were isolated from the culture broth of Paecilomyces variotii , a fungus acquired from the giant jellyfish Nemopilema nomurai , which was collected from the South Korean Sea .…”
mentioning
confidence: 99%